Blindness in a Woman With Human Immunodeficiency Virus Infection and Syphilis - Michael Luchi; Curtis Beauregard; Kevin Ault; Daniel Hinthorn (Hindawi Limited, 1995)
Background: A concomitant infection with human immunodeficiency virus (HIV) may alter the natural history of other infections. Several reports indicate that syphilis may behave more aggressively when HIV infection is present.